Pendampingan EPS-TOPIK (Employment Permit System–Test of Profciency in Korean) bagi Calon Pekerja Migran Indonesia dari Propinsi D.I. Yogyakarta - Suray Agung Nugroho (Bakti Budaya: Jurnal Pengabdian kepada Masyarakat, 2019)
The relatively low numbers of Indonesian migrant workers who passed the EPS-TOPIK (Employment Permit System–Test of Profciency in Korean) as a prerequisite to work in Korea as well as the relatively small numbers of Korean language instructors with experiences and backgrounds in Korean language teaching are the rationales that prompted Korean Language and Culture Program, Faculty of Cultural Sciences UGM to carry out this Community Engagement Activity. As an initial engagement, we carried out an EPS TOPIK Try Out test to 48 migrant worker candidates who currently learn Korean language at 5 Korean Language Courses in Yogyakarta Province. Tis is the frst engagement activity planned to be carried out continuously as our endeavor to solve the aforementioned problems. Based on the results of the Try Out test, we observed that they need to brush up their Korean competency in understanding Korean conversations and in using vocabularies in the right context. We will use these initial fndings as a basis to make a Learning and Teaching Material suitable for both the learners and the instructors. We plan to make the materials by incorporating both the learners and the instructors’ difculties in learning and teaching Korean language with EPS-TOPIK as the starting point. It is also worth to note that in many Korean Language Courses across the country, the main Korean language instructors are the returned migrant workers themselves. Albeit being able to write and talk in Korean, they had no prior educational background of Korean language. Tus, we also plan to continue setting up methods to teach them Korean language in a series of Training for Trainers program (the next Community Engagement Activities) in cooperation with related institutions like BNP2TKI (Agency for the Protection and Placement of Indonesian Migrant Workers). We deem it necessary to go on with the plan as the Government to Government Agreement between Korea and Indonesia in dispatching Indonesian migrant workers to Korea is still in eﬀect.  =================================================================Belum maksimalnya tingkat kelulusan para calon pekerja migran Indonesia (PMI) dalam ujian EPS-TOPIK (Employment Permit System–Test of Profciency in Korean) serta masih kurangnya jumlah pengajar bahasa Korea yang berlatar belakang pengajaran bahasa Korea di lembagalembaga pelatihan bahasa Korea mendorong Prodi Bahasa dan Kebudayaan Korea FIB UGM untuk memulai sebuah kegiatan Pengabdian kepada Masyarakat (PkM) dengan tema yang  berkaitan dengan problema tersebut. Untuk itulah, sebagai langkah awal, prodi mengadakan try out ujian EPS-TOPIK kepada 48 calon PMI yang tengah belajar bahasa Korea di lima Lembaga Kursus & Pelatihan (LKP) Bahasa Korea di Provinsi DIY. Kegiatan ini adalah PkM perdana yang didesain untuk dilaksanakan secara berkelanjutan sebagai kontribusi langsung dalam pemecahan masalah. Berdasarkan hasil try out yang menunjukkan masih perlu ditingkatkannya kemampuan bahasa Korea para peserta, terutama dalam hal memahami percakapan dan pemakaian kosakata secara tepat, maka prodi berencana untuk menggunakan hasil ini sebagai landasan untuk membuat bahan ajar terkait EPS-TOPIK yang dapat digunakan oleh peserta didik ataupun para pengajar dalam mempelajari dan mengajarkan materi-materi dalam EPSTOPIK (Rencana PkM tahap 2). Selanjutnya, prodi bekerja sama dengan BP3TKI dan instansi lainnya berencana untuk menyelenggarakan Training of trainers, yaitu lokakarya pengajaran bahasa Korea untuk para pengajar bahasa Korea di LKP LKP seluruh Indonesia (Rencana PkM tahap 3). Semua itu didasari dengan fakta bahwa kerja sama Goverment to Government (G to G) antara Korea dan Indonesia dalam pengiriman PMI terus berjalan. Oleh karena itu, kegiatan PkM berkelanjutan ini didesain untuk memberikan sumbangan awal prodi dalam mengatasi rendahnya penyerapan calon PMI ke Korea yang disebabkan oleh rendahnya kemampuan bahasa Korea para calon PMI.